Green Synthesis of Chitosan from Aspergillus niger and Evaluation of Antioxidant Property and Cytotoxic Effects on Selected Cancer Cell Lines - Hungund, Basavaraj S.; Tennalli, Gururaj B.; Gachhi, Dhanashree B.; Shiralgi, Yallappa (Asian Journal of Chemistry, 2025)
Chitin and chitosan, derived from fungal cell walls, possess significant biomedical importance due to their unique material properties. Chitin and chitosan were extracted from Aspergillus niger strains (BSH5 and BSH9) using a two-phase extraction method. The biopolymers were characterized by FTIR, X-ray diffraction (XRD), 1H NMR spectroscopy and scanning electron microscopy (SEM). The thermal stability of chitin and chitosan was studied using thermogravimetric/differential scanning calorimetry (TGA-DSC). Fourier transform infrared (FTIR) was used to analyze the functional groups and validate the composition of the materials. The broad absorption band corresponding to the hydrogen-bonded O-H absorption band overlapped with the N-H band. 1H NMR also confirmed the purity of the biopolymers. X-ray diffraction (XRD) patterns of chitin and chitosan show the semi-crystallinity, a potential layered crystalline structure and a similar pattern to the commercial polymers. TGA-DSC analyses demonstrated the thermal stabilities of chitin and chitosan. Structural morphology by scanning electron microscopy (SEM) revealed thick and rough surfaces indicating the presence of amorphous nature of the material. Antioxidant studies revealed the radical scavenging activity of 46.38% and 47.65% for strains BSH5 and BSH9, respectively. Chitosan from both the stains demonstrated significant cytotoxic effect against MCF7 cell line with IC50 values of 206.6 µg/mL and 244.7 µg/mL, respectively. The material characterization and biological attributes demonstrated potential biomedical applications of the prepared biopolymer chitosan.